Reanimated voices : speech reporting in a historical-pragmatic perspective - Collins, Daniel E. (Amsterdam ; Philadelphia, PA : John Benjamins Pub., 2001)
Reanimated Voices addresses three activities: reporters evoking speech events; interpreters (re)constituting those speech events; and historical pragmaticians eavesdropping in time on the reporters and interpreters. Can one reconstruct aspects of pragmatic competence on the basis of written texts only? Reanimated Voices answers this in the affirmative. It offers a methodology for historical-pragmatic reconstruction to explain the synchronic patterns of variation in premodern writings. Reanimated Voices examines the distribution of reporting strategies in a corpus of medieval Russian texts. For.
REANIMATED VOICES; Editorial page; Title page; LCC data; Dedication; Table of contents; Acknowledgments; Preface; The pragmatics of reported speech; The text-kind: A pragmaphilological overview; Testimony; Residual forms in testimony; The question framework; Reporting from judicial-referral hearings; Layered reports; Reporting the verdict; Conclusions; Notes; References; Appendix: Text-kind and date of the investigated trial transcripts; Name index; Subject index; PRAGMATICS AND BEYOND NEW SERIES.
Includes bibliographical references (pages 319-342) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Grammar, Comparative and general -- Indirect discourse; Pragmatics; Trial transcripts; Discours indirect; Pragmatique; Procès -- Sténographies.; pragmatics; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammar, Comparative and general -- Indirect discourse; Pragmatics; Trial transcripts; Russisch; Historische taalwetenschap; Pragmatiek; Rechtspraak; Rechtstaal; Trial and arbitral proceedings; Trial and arbitral proceedings; Comptes rendus de procès et d'arbitrage.